ANALYSIS OF LIGHTING UTILITY SYSTEM COMPLIANCE IN THE LIBRARY OF SMP NEGERI 4 MALANG CITY - Achmad Zidan Dwi Ismail; Nur Latifah Khomsiati; Adilla Rava Naura Ayu; Ahmad Affan Firza Alfian; Tee Tze Kiong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the compliance of the lighting utility system in the library of SMP Negeri 4 Malang City against the Indonesian National Standard SNI 6197:2011. A quantitative descriptive method with a case study approach was employed, using direct lux meter measurements at 80 grid points (A1–H10) conducted between 13:00 and 15:00 under clear weather conditions to capture optimal natural lighting data. Results indicate that illuminance levels range from 135.40 lux to 355.50 lux; however, the distribution is highly non-uniform. Only Zone A, located nearest to the primary openings, consistently meets the 300 lux minimum standard, while more than 75% of the measured area falls below this threshold and is classified as under-lit. Contributing factors include restricted natural light penetration, a solid wall on the eastern façade blocking that light path, and dense interior shelving that obstructs light propagation toward central and rear zones. The study concludes that the current lighting system does not fully satisfy SNI 6197:2011 requirements, and recommends the addition of artificial lighting fixtures, optimization of interior furniture layout, and enhancement of façade opening design to improve visual comfort for library users